Immunological changes induced by ovaprim in the freshwater catfish, Heteropneustes fossilis (Bloch) - Dash, Kalpana; Singh, B N; Pandey, A K; Ayyappan, S (Indian Journal of Fisheries, 2011)
Haemagglutination assay (HA), humoral-mediated specific immune response andalternative pathway of complement-mediated haemolysis (APCH50) were performedto evaluate the immunological responses of the synthetic hormone drug ovaprimin Heteropneustes fossilis. It was found that ovaprim suppresses the haemagglutininas well as the specific antibody titres of the catfish sera against rabbiterythrocytes (RaRBCs) and bovine serum albumin (BSA) antigen while combinationwith |3-glucan restored its normal activity indicating its immunomodulatory effect.Furthermore, APCH50 unit of fish sera was remarkably decreased by ovaprimtreatment. Anti-ovaprim antibody could not be detected in serum of the treatedcatfish.